Caracterização do desenvolvimento ontogenético de Steindachneridion melanodermatum (Garavello, 2005) (pisces, siluriformes) da Bacia do Rio Iguaçu, Brasil - Sereia, Diesse Aparecida de Oliveira (2010)
The species Steindachneridion melanodermatum is an endemic fish to the Iguaçu River basin. Has great potential for pisciculture, however its initial development is still unclear, which limits the progress in the cultivation of this species. In this way, this study aimed to characterize the development ontogenetic of Surubim-do-iguaçu. The eggs larvae were obtained by induced spawning performed at the Experimental Station of Ichthyological Studies of the Ney Braga Power Plant (Salto Segredo Power Plant), Energy Company of Paraná (COPEL), between the months of January to March 2009. The morphometric and meristic variables were analyzed in 529 eggs, 370 larvae in preflexion, flexion and postflexion stages, and 117 juveniles. The eggs are spherical, transparent and non-adhesive, have an average diameter of 3.17 mm, perivitelline space of 0.96 mm and 2.12 mm calf. The larvae hath 33 hours and 30 minutes after fertilization (26.5° C). The larvae have a fusiform body without pigmentation initial, median eyes, intestine that goes beyond the middle portion of the body and the number of total myomeres ranged from 42 to 48. The juveniles resemble an adult, with a standard length of 28.43 mm and pigmentation formed by chromatophores punctiform irregularly distributed throughout the body